2014
DOI: 10.1055/s-0033-1364183
|View full text |Cite
|
Sign up to set email alerts
|

Identification of p.W246L As a Novel Mutation in the GP1BA Gene Responsible for Platelet-Type von Willebrand Disease

Abstract: Platelet-type von Willebrand disease (PT-VWD) and type 2B von Willebrand disease (2B-VWD) are rare bleeding disorders characterized by increased ristocetin-induced platelet aggregation (RIPA) at low concentrations of ristocetin. Diagnosis of either condition is not easy and the differential diagnosis between the two entities is especially challenging as evidenced by high levels of misdiagnosis of both conditions, but particularly PT-VWD. Five mutations in the GP1BA gene related to PT-VWD and less than 50 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
25
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 39 publications
1
25
0
Order By: Relevance
“…Other mutations in the GP1BA gene have been described so far, M239V (Russell & Roth, ), G233S (Matsubara et al , ), a 27‐bp in‐frame deletion (Othman et al , ), D235Y (Enayat et al , ) and W246L (Woods et al , ). All of these mutations induce a gain of function resulting in an enhanced affinity for VWF and enhanced platelet aggregation to a low dose of ristocetin (0·5 mg/ml), which normally does not induce platelet agglutination.…”
Section: Classical Inherited Macrothrombocytopenias That Are Identifimentioning
confidence: 99%
“…Other mutations in the GP1BA gene have been described so far, M239V (Russell & Roth, ), G233S (Matsubara et al , ), a 27‐bp in‐frame deletion (Othman et al , ), D235Y (Enayat et al , ) and W246L (Woods et al , ). All of these mutations induce a gain of function resulting in an enhanced affinity for VWF and enhanced platelet aggregation to a low dose of ristocetin (0·5 mg/ml), which normally does not induce platelet agglutination.…”
Section: Classical Inherited Macrothrombocytopenias That Are Identifimentioning
confidence: 99%
“…A shorter survival indicated by an increased VWFpp: VWF ratio in patients with type 2B VWD was reported, where an enhanced affinity of the abnormal VWF to normal platelet GPIbα is observed. 19 In their report, 1 Woods et al showed that the VWFpp and VWFpp:VWF ratio were unexpectedly normal in PT-VWD Try246Leu mutation. This may indicate that the clearance and survival of VWF may be two different mechanisms in patients with PT-VWD.…”
mentioning
confidence: 94%
“…We are pleased to highlight in this issue of Seminars in Thrombosis & Hemostasis, the study by Wood et al, 1 wherein the authors describe a novel mutation in the platelet GP1BA gene creating a hyperresponsive GPIbα protein-a receptor for von Willebrand factor (VWF)-and causing platelet-type von Willebrand disease (PT-VWD). This is a new naturally occurring mutation in a 23-year-old male patient and is considered the sixth reported mutation thus far in patients described with this disease worldwide.…”
mentioning
confidence: 99%
See 2 more Smart Citations